Determinants of work-life balance among academic staff in Universiti Teknologi MARA (UiTM) Perlis - Omar, Siti Nur Zahirah; Rozali, Muhammad Aqil Hamzi; Abdullah, Nur Iman Nadhirah; Mohd Kamal Azizi , Amirun Adli; Mohd Zaimi, Muhammad Aidil Syairazi; Supardi, Nur Shireen (Journal of Islamic, Social, Economics and Development, 2026)
There have been numerous concerns on the topic of work-life balance within higher institutions of learning since it is influenced by increased workloads, extended working hours, technology development, and workplace stress which might have adverse effects on the well-being and performance of employees. This research seeks to identify the factors affecting the work-life balance among the academic staff members at Universiti Teknologi MARA (UiTM) Perlis by determining the correlations between workload, organizational support, working hours, job demands, workplace stress, and work-life balance. To conduct the research, a quantitative cross-sectional approach will be used with the help of questionnaires designed for the sample of 248 academic staff members selected through simple random sampling from a population of 674 people. The questionnaire uses a five-point Likert scale, and the obtained data will be analyzed using SPSS 27 with the help of descriptive statistics, Pearson correlation, and simple linear regression analysis.